Novel mathematical analysis on CSSN parameters for various fading effects - Naveen Kumar Boddukuri; Debasish Pal; Ayan Kumar Bandyopadhyay; Chaitali Koley (Results in Engineering)
This research investigates the performance of Cooperative Spectrum Sensing (CSS) networks in diverse fading environments, employing various soft data combining techniques. Assuming a non-faded reporting channel and impact of fading effects on sensing channel performance using conventional energy detection. The objective of this paper is to determine which diversity technique maximizes the average detection probability under various fading conditions. We have also aimed to identify which fading environment is giving a higher detection probability value. Theoretical expressions are derived and validated through MATLAB simulations, with results presented as signal-to-noise ratio (SNR), average detection probability, and complementary receiver operating characteristic (CROC) curves. A comparative analysis of diversity techniques is provided, identifying the most effective approach for CSS networks in challenging fading environments.